Exploring the relationship between strategic planning and educational performance: a systematic literature review - Endo, Semail; Busari, Abdul Halim; Ibrahim, Dayang Kartini Abang (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the evolving landscape of education, strategic planning has emerged as a critical tool for enhancing institutional performance and achieving educational excellence. This systematic literature review aims to explore the intricate link between strategic planning and educational performance by synthesizing findings from a diverse array of studies. The review addresses the pressing need for a structured approach to improving educational outcomes. To achieve this, we conducted an extensive search of scholarly articles from reputable databases such as Scopus and Web of Science, focusing on studies published between 2020 and 2024. The flow of the study based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework. The database found (n=28) final primary data was analyzed. The finding was divided into three themes which are: i) competency development and assessment in education; ii) strategic planning and management in higher education; and iii) technological integration and innovation in education. The results highlight the significance of implementing a comprehensive and flexible framework for strategic planning that aligns with the specific requirements and environments of educational institutions. In conclusion, this research offers insightful information to educators, administrators and policymakers who want to use strategic planning to support long-term improvements in student performance and eventually advance the larger objective of educational excellence.